Developing a Bilingual E-Guidebook for Pura Puseh Desa Batuan as a Tourist Travel Media - Waqidhatus Sya'diyah; Achmad Suyono (UPT P2M Politeknik Negeri Malang, 2026)
Pura Puseh Desa Batuan is a cultural heritage site in Gianyar, Bali, that is frequently visited by both domestic and foreign tourist. However, the site of the temple lacks detailed information. In this research aimed to develop a bilingual e-guidebook as a travel media to assist the visitors in discovering spots, and increase the readers knowledge. The research used the Design and Development Research (DDR) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observation, interviews, and documentation. The e-guidebook was created using Canva Pro, consists of 100 pages presented in Indonesian and English. The content of e-guidebook included history, temple areas, cultural heritage, facilities, local arts, and accommodations. The product was validated by language, design, and content experts, and field-tested with 56 respondents filled by local and foreign respondents. Field testing also showed positive feedback, with an overall average score of 3.65. The findings demonstrate that the bilingual e-guidebook is informative, user-friendly, and supports tourism development in Pura Puseh Desa Batuan.